Challenges faced by primary caretakers of adolescent girls with intellectual disability during their menstrual cycle in Puducherry: A mixed method study - S Karthikayini; S Arun (Wolters Kluwer Medknow Publications, 2021)
Background: Adolescents with Intellectually Disability (ID) compared to their normal peers face greater challenges at menarche due to their caregiver dependence for their day-to-day personal care activities. Objective: The objective of the study was to know the sociodemographic characteristics of adolescent girls with ID and to explore the challenges faced by their primary caretakers during their menstrual cycle in Puducherry. Subjects and Methods: The study was conducted among primary caretaker of adolescent girls with ID from December 2018 to May 2019. The study adopted quantitative method to capture sociodemographic details among 73 primary caretakers of adolescent with ID who attained menarche and In-Depth Interview (IDI) was conducted to explore the challenges faced by primary caretakers. The caretakers of adolescents were selected using purposive sampling and conventional content analysis was followed for data analysis. Results: We discovered that 80.9% of adolescent with ID were not able to manage their menstruation of their own. Primary caretakers who were interviewed were mostly mother's 67.1%. Due to caretaker's dependency, 94.5% of the adolescent with ID were not going to school during their menstrual cycle. Conclusions: Majority of the caretakers faced problems such as rejection of sanitary napkins and inability to recognize about the start of period by their adolescents with ID.